Study on BSS Algorithm used on Fault Diagnosis of Gearbox - Yu Chen; Jintao Meng (Institute of Advanced Engineering and Science, 2013)
The gearbox is a complicated rotating machinery equipment, in order to realize the gearbox fault early detection and prevention, it is the key to carry out the online diagnosis. This paper used the adaptive variable step-length natural gradient blind source separation algorithm to realize the helicopter gearbox meshing vibration signal and fault vibration signal effective separation. Through the algorithm simulation, the accuracy of the algorithm gained the verification and the separation error trended to zero, which has higher separation precision. This algorithm can realize the complicated mechanical vibration signal blind source separation and fault diagnosis, which has a broad application prospect. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2260